Decentralising Zimbabwe’s water management: The case of Guyu-Che- lesa irrigation scheme - Tambudzai, Rashirayi; Everisto, Mapedza; Gideon, Zhou (Physics and Chemistry of the Earth, 2013)
Smallholder irrigation schemes are largely supply driven such that they exclude the beneficiaries on the management decisions and the choice of the irrigation schemes that would best suit their local needs. It is against this background that the decentralisation framework and the Dublin Principles on Integrated Water Resource Management (IWRM) emphasise the need for a participatory approach to water manage- ment. The Zimbabwean government has gone a step further in decentralising the management of irriga- tion schemes, that is promoting farmer managed irrigation schemes so as to ensure effective management of scarce community based land and water resources. The study set to investigate the way in which the Guyu-Chelesa irrigation scheme is managed with specific emphasis on the role of the Irrigation Management Committee (IMC), the level of accountability and the powers devolved to the IMC. Merrey’s 2008 critique of IWRM also informs this study which views irrigation as going beyond infrastructure by looking at how institutions and decision making processes play out at various levels including at the irrigation scheme level. The study was positioned on the hypothesis that ‘decentralised or autonomous irrigation management enhances the sustainability and effectiveness of irrigation schemes’. To validate or falsify the stated hypothesis, data was gathered using desk research in the form of reviewing articles, documents from within the scheme and field research in the form of questionnaire surveys, key informant interviews and field observation. The Statistical Package for Social Sciences was used to analyse data quantitatively, whilst content analysis was utilised to analyse qualitative data whereby data was analysed thematically. Comparative analysis was carried out as Guyu-Chelesa irriga- tion scheme was compared with other smallholder irrigation scheme’s experiences within Zimbabwe and the Sub Saharan African region at large. The findings were that whilst the scheme is a model of a decen- tralised entity whose importance lies at improving food security and employment creation within the community, it falls short in representing a downwardly accountable decentralised irrigation scheme. The scheme is faced with various challenges which include its operation which is below capacity utilisa- tion, absence of specialised technical human personnel to address infrastructural breakdowns, uneven distribution of water pressure, incapacitated Irrigation Management Committee (IMC), absence of a locally legitimate constitution, compromised beneficiary participation and unclear lines of communica- tion between various institutions involved in water management. Understanding decentralization is important since one of the key tenets of IWRM is stakeholder participation which the decentralization framework interrogates.